Marketing capabilities of fashion and apparel retailing among small medium enterprises in Bangi / Nurul Syazana Mohd Razi - Mohd Razi, Nurul Syazana (Faculty of Business and Management, 2018)
Intense competition on short product life cycles in fashion retailing present a number of marketing challenges for retail firms. In order to survive in this industry it is vital for participants to develop and leverage marketing capabilities. Marketing capabilities used by many firms to maintain firm performances. The main study of this research is to investigate the marketing capabilities among SME fashion and apparel retailer in Bangi. Firm performance being a dependent variables in this research and measured by four independent variables which is customer service, store image differentiation, promotional capability and ICT adoption. A review of literature was conducted to find out the firm performance on fashion and apparel retailer. The literature review showed the relationship. This research is based on 67 respondents which collected in Bangi. Sampling method used in this study is convenience sampling. The data was analyzed using correlation coefficient and regression by using SPSS software. The findings showed that are positive relationship between these marketing capabilities and firm performance. However, the result showed that customer service, store image differentiation and promotional capability has significant impact on firm performance.